Mapeamento sobre modelagem matemática no Ensino Médio no período de 2017 a 2020 - Barioni, Alexandra Aguiar (2022)
This dissertation presents a research carried out within the scope of the Academic Master's Program of Postgraduate Studies in Mathematics Education at PUC-SP. It is a state-of-the-art bibliographic theoretical research that aims to elaborate a Research Panorama that has as its theme the use of mathematical modeling in High School: from 2017 to 2020. The objective of the Panorama is to systematize the two main elements of a modeling: the phenomenon to be modeled and the modeling mathematical concept. Data were selected from the search for dissertations and articles using the Google search engine. The study included the analysis of 11 articles and 6 dissertations. It was observed that of the 17 works analyzed, 5 of them used function as a modeling concept, and plane geometry, spatial geometry, trigonometric function, quadratic function, numerical sets, matrices, differential equation, differential equation system and statistics were presented. as a phenomenon to be modeled, for example, calculate the area of the lake, analysis of inflation in the year 2015, calculate the volume of cake dough that would fit in a form, orange peel in fuel production, what are the take-off and lift procedures of an aircraft, temperature Variation, cooling or heating of food for consumption, among others